2015
DOI: 10.1108/jfm-09-2013-0049
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking challenges in facilities management in Nigeria

Abstract: Purpose – The paper aims to examine benchmarking challenges among Nigerian Facilities management (FM) practitioners. Design/methodology/approach – Data collection was through self-administered questionnaires sent to 120 FM organizations in Lagos metropolis, 50 in Abuja and 15 in Port Harcourt. Also, interviews were conducted on six facilities managers to ascertain challenges faced by organizations that use best practice benchmarking. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Ever since then, it has witnessed tremendous global transformation, entering Europe in the mid-1980s, first in the UK in 1984, The Netherlands in 1986, the Scandinavian countries in 1992 and Germany in 1995 (Levainen, 1997). As a follow-up to this, a non-profit organisation called the International Facilities Management Association (IFMA) was established in the early 1980s to incorporate associations dedicated to serving the FM profession originally in North America; however, as of today, it has globally represented members from over 60 countries worldwide (Ventovuori, 2007), including Nigeria, where it offers guidance and expertise to its members, as well as carrying out research to substantiate best practice in FM (Adewunmi et al, 2008).…”
Section: The Concept Of Fmmentioning
confidence: 99%
“…Ever since then, it has witnessed tremendous global transformation, entering Europe in the mid-1980s, first in the UK in 1984, The Netherlands in 1986, the Scandinavian countries in 1992 and Germany in 1995 (Levainen, 1997). As a follow-up to this, a non-profit organisation called the International Facilities Management Association (IFMA) was established in the early 1980s to incorporate associations dedicated to serving the FM profession originally in North America; however, as of today, it has globally represented members from over 60 countries worldwide (Ventovuori, 2007), including Nigeria, where it offers guidance and expertise to its members, as well as carrying out research to substantiate best practice in FM (Adewunmi et al, 2008).…”
Section: The Concept Of Fmmentioning
confidence: 99%
“…In a more recent study, Adewunmi, Omirin, and Koleoso (2015) examined the benchmarking challenges in Nigerian Facilities management. They found that implementation of benchmarking faces many obstacles such as, lack of understanding of the exercise of benchmarking, unwillingness to change, weakness of data from other organizations and poor execution of the benchmarking exercise.…”
Section: The Relationship Between Benchmarking and Organizational Permentioning
confidence: 99%
“…According to Adewunmi et al (2008), the practice of benchmarking is limited in Nigeria because many organizations tend not to link strategic vision with the need to benchmark, inability to appreciate benefits of benchmarking as a result of lack of proper orientation about it. In addition, many FM organizations lack processes for data management, and benchmarking is used to measure performance informally rather than as a distinct process reliant on performance criteria.…”
Section: Fm Benchmarking In Nigeriamentioning
confidence: 99%
“…Also, some types of facilities like retail and hotels were excluded from the study. Adewunmi et al (2013) in Nigeria examined the application of benchmarking among Nigerian FM practitioners. Data collection was through self-administered questionnaires sent to 120 FM organisations in Nigeria.…”
Section: Categories Of Benefits Of Benchmarkingmentioning
confidence: 99%